Menerapkan Tindak Tutur untuk Meningkatkan Kemampuan Kognitif Siswa - Adriansyah Abu Katili (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
This activity aims to provide theoretical and practical knowledge on the application of speech acts to develop students’ cognitive abilities among teachers at Madrasah Tsanawiyah Muhammadiyah Kabila. The activity was conducted in the form of a seminar with teachers as participants. The seminar materials covered knowledge of speech acts and cognitive abilities based on Bloom’s Taxonomy. Through this knowledge, teachers are expected to be able to apply appropriate speech acts in accordance with the level of cognitive ability expected to be achieved by students. This activity is an implementation of the Text and Discourse Analysis course.